ATIM-06. TREATMENT OF RECURRENT/REFRACTORY (R/R) ANAPLASTIC ASTROCYTOMA (AA, WHO GRADE 3) PATIENTS WITH ANTI-TGFß2 RNA THERAPEUTIC OT-101 VERSUS TEMOZOLOMIDE IS ASSOCIATED WITH IMPROVED OVERALL SURVIVAL. (11th November 2019) - Uckun, Fatih; Qazi, Sanjive; Nam, David; Hwang, Larn; Trieu, Vuong
Abstract: BACKGROUND: OT-101 is a first-in-class RNA therapeutic designed to disrupt the immunosuppressive action of TGFß2. During Phase 1 clinical trials, OT-101 induced partial responses in R/R AA patients. We now report our clinical results from a randomized Phase IIB study (NCT00431561) that further evaluated its single agent activity in R/R AA patients in side-by-side comparison with the standard chemotherapy drug temozolomide (TMZ). METHODS: OT-101 was administered via high-flow microperfusion with an intratumoral catheter using a convection enhanced delivery (CED) system. 26 AA patients (12: 2.5 mg/cycle; 14: 19.8 mg/cycle) received 7-day cycles of OT-101 every other week via continuous infusion for 4–11 cycles. Response determinations were based on central review of MRI scans by an independent review committee according to standard as well as modified McDonald criteria. 11 patients in the active control arm were treated with TMZ (150–200 mg/m 2, 5 days/28-day cycles x up to 6 treatment cycles). Standard statistical methods were applied for the analysis of data. RESULTS: 14 of 26 patients (53.8%) treated with 4–11 cycles of OT-101 had either a CR (N=2) or PR (N=12) as their best overall response. The average time until 99% reduction of their tumor volumes ranged from 9.9 to 115.4 (median: 23.7) months. In contrast, only 1 of 10 evaluable patients (10%) treated with TMZ achieved an objective response which was a PR (Fisher's exact test, 2-tailed, P-value = 0.0002). The median overall survival (OS) was 1154 days (95% CI: 811 - >1743) for the OT-101 group and 590 days (95% CI: 287 - >1137) days for the TMZ group (Log Rank Chi Square = 7.55, P-value = 0.006). CONCLUSION: Our results confirm and extend previous studies and provide early evidence that the anti-TGFß2 RNA therapeutic OT-101 is at least as active as TMZ in salvage therapy of R/R AA patients.